Śrīrāmacaritamānasa : kathāsāra : Rāmacaritamānasa upara Bhāratanā Pradhāna Mantrī Śrī Morārajībhāī Desāīe tārīkha 14-10-ʼ77thī 17-10-ʼ77 sudhī Gūjarāta Vidyāpīṭha, Amadāvādamāṃ āpela pravacana - Desai, Morarji, 1896-1995 (Gujarāta Vidyāpīṭha, 1978)
Lectures on Rāmacaritamānasa by Tulasīdās, 1532-1623, delivered at Gujarat Vidyapith, Ahmedabad, Oct. 1977.